CsNatterin-3 serves as a pattern recognition molecule that activates the peripheral blood leukocytes of Cynoglossus semilaevis against bacterial infection - Pei-yuan Gao; Xuan-yue Wang; Xin-yi Jiang; Yipaerguli Yalikun; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2027)

PoGPx-7, a glutathione peroxidase homolog from teleosts, exhibits bactericidal activity and activates host immune cells against bacterial infection - Xin-yi Jiang; Xue-pin Han; Jia-hang Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2026)

Optimized straw–nitrogen management enhances crop yield, soil carbon sequestration, and economic returns in dryland maize systems of Northwest China - Yunfei Ren; Jiayi Li; Fu Liu; Longchuang Zhang; Xiu Chen; Haibo Hu; Xiaoyu Ning; Yeye Zhang; Jinxia Wang; Xiaozhou Li; Shuangguo Zhu; Fei Mo (Soil and Tillage Research, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Stable colloidal dispersion cross-linked Janus hydrogel films for simultaneous efficient uranium capture and seawater desalination - Huilian Mo; Jing Wang; Jingyu Yu; Ziyang Wang; Siyi Wang; Fei Wu; Suwen Chen (Journal of Hazardous Materials, 2026)

Crafting a savory seafood paste from defatted Antarctic krill meal via synergistic enzymatic hydrolysis and Maillard reaction - Lingzhao Wang; Gaoqin Mo; Wenhu Zhen; Yingcai Zhao; Yuchengmin Zhang; Fei Li; Shuangtong Wang (International Journal of Gastronomy and Food Science, 2026)

Bioaugmentation of Rhodococcus ruber F1 achieved simultaneous removals of benzophenone-3 and ammonium - Fei Liu; Chenyu Li; Yuxuan Zhou; Mo Li; Zhicheng Pan; Fu Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2026)

Genome-wide association study uncovers the genetic loci for yield-related traits in waxy rice - Yunyan Fei; Zhenghai Mo (Journal of Applied Genetics, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Retraction notice to “Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices” [Sci. Total Environ. 925 (2024) 171564] - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Single-cell and spatial transcriptomics identify PGK1-sensitized hypoxia macrophages as a therapeutic target to overcome PDT resistance in glioma - Xiuwei Yan; Jiahe Hu; Xuyan Han; Lei Xu; Lihui Zhou; Jiaoyan He; Fei Yang; Longgang Zhou; Yapeng Niu; Mo Geng; Wenjie Yuan; Dong Zhao; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

38 years of micronutrient fertilization, particularly copper, enhance winter wheat yield during drought on the Loess Plateau without yield penalties - Xiaozhou Li; Fu Liu; Yunfei Ren; Jinxia Wang; Haibo Hu; Shuangguo Zhu; Fei Mo (Field Crops Research, 2026)

Wind tunnel study of wind flow over low- to high-rise building arrays using PIV and POD analysis - Yunming Zhang; Ziwei Mo; Fei Li; Ruiqi Wang; Guoliang Chen; Shiyun Liu; Yixun Liu; Chun-Ho Liu (Building and Environment, 2026)

Comparative evaluation of BacT/ALERT PF Plus and PF pediatric blood culture bottles: A dual in vitro and clinical retrospective study - Shanshan Ma; Weilong Kong; Meng Duan; Fei Mo; Weiping Lu; Qiu Zhong (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Presence of per- and polyfluoroalkyl substances (PFASs) in the Nandu River Estuary, Hainan Island - Jiang-Wei Miao; Zhang-Min Jiang; Peng-Fei Xie; Jia-Xing He; Jia Xie; Hai-Long Zhou; Ling-Mo; Shi-Quan Chen; Tuan-Tuan Wang; Sai Wang (Marine Environmental Research, 2026)

The combined exposure exacerbates the toxic effect of cadmium and uranium on rice seedlings - Jun Liu; Meihan Cai; Jiajie Zhang; Aili Mo; Shiyu Hu; Peishuang He; Menglei Jiang; Wei Zhao; Cuiying Peng; Tangjian Peng; Fei Yang (Journal of Environmental Sciences, 2026)

Laser-biomimetic patterned CFRP with hierarchical structures achieves high EMI shielding performance - Zhonghe Wang; Chao Niu; Di Liu; Shuwei Sun; Yujie Wang; Mo Zhang; Chunting Wu; Changqing Li; Fei Chen; Junjie Sun; Zhulong Huang; Yao Ma; et al. (Chemical Engineering Journal, 2026)

Nitrogen pollution alters bacterial carbonate mineralization potential in karst river - Jing Mo; Zining Guo; Mengqi Shao; Zhibo Hu; Fei Liu; Xiangyu Guan (Journal of Environmental Management, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Coupled effects of rainfall-induced soil moisture and nitrogen placement depth on maize productivity and resource utilization in the Loess Plateau - Fu Liu; Peng Wu; Yajuan Li; Shengtong Ma; Nannan Li; Fei Mo; Zhikuan Jia (Field Crops Research, 2025)

Synthesis of CaCO3 microspheres modified by glycine and ethylene glycol for adsorption removal of Cd(II) - Jinyun He; Mingbiao Gun; Yanwu Wang; Shuyi Mo; Fei Long (Environmental Research, 2025)

Global Change Alters the Abundance and Community Structure of Arbuscular Mycorrhizal Fungi and Influences Plant Mycorrhizal Benefit - Ai‐Tian Ren; Meng‐Li Wang; He‐Miao Gao; Bede S. Mickan; Long‐Yi Yuan; Si‐Kun Liu; Shao‐Cong Zhang; Lynette K. Abbott; You‐Cai Xiong; Fei Mo (Global Ecology and Biogeography, 2025)
Aims Arbuscular mycorrhizal (AM) fungi play critical roles in ecosystem services and exhibit sensitivity to global change factors (GCFs). However, the interactive effects of multiple GCFs on AM fungal communities, and whether changes in AM fungal communities have a feedback effect on plant–mycorrhizal benefits under global change remain poorly understood. Location Global. Time Period 1990 – 2022. Major Taxa Studied Arbuscular mycorrhizal fungi; arbuscular mycorrhizal plant hosts. Methods We synthesised 1646 observations of arbuscular mycorrhizal (AM) fungal communities from field experiments to evaluate how manipulated GCFs affect their abundance and community structure and to determine the potential consequences for outcomes of plant–mycorrhizal fungal relationships. Results The interactive effects among GCFs were mainly additive rather than synergistic or antagonistic. AM fungal diversity was not consistently sensitive to the individual effects of GCFs; however, a significant shift in community structure occurred under individual or concurrent GCFs. When multiple factors were imposed simultaneously, their negative effect on AM fungal colonisation was strengthened, while their effects on community structure were diminished. Moreover, plant performance was closely linked to changes in abundance and community structure of AM fungi under GCFs. Experimental duration and environmental variables emerged as the most important predictors of AM fungal responses to GCFs. Conclusions Reordering or replacement of AM fungal species has been identified as the key mechanism driving community responses to GCFs. Our study highlights the need to monitor AM fungal community structure and associated functional consequences for plant communities under ongoing global change.

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

First observation of biochar aerosol generation from raindrop impact on biochar-amended soils - Zhiao Li; Mo Zhang; Xinyuan Deng; Yiwen Wang; Fei Lian (Journal of Hazardous Materials, 2025)

Reducing nitrogen application through deep placement to optimize the nitrogen balance in a dryland maize cropping system - Fu Liu; Haibo Hu; Xue Li; Zhikuan Jia; Fei Mo (Journal of Cleaner Production, 2025)

Crumpled polyamide membranes templated by macroporous scaffolds for ultra-permeable nanofiltration - Hao Zhang; Fei Xie; Zhe Yang; Zhonghao Xu; Jia-Wei Mo; Xiao-Hua Ma; Zhen-Liang Xu (Desalination, 2025)

Closing the loop with citramalic acid-based chiral polyester: A novel strategy as a game-changer for sustainable materials - Lei Song; Xinyu Liu; Ruimin Wang; Mo Zhou; Fei Li; Yunlong Sun; Lu Li; Yanming Hu; Ding Zhou; Xiaowei Xu; Mingyuan Zheng; Rui Wang (Chemical Engineering Journal, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Cropping pattern switching induces disturbances in spatiotemporal greenhouse gas emissions and water demand - Yihe Tang; Shikun Sun; Fei Mo; Thomas W. Crowther; Yali Yin; Jinfeng Zhao; Yubao Wang; Pute Wu (European Journal of Agronomy, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Do Microplastics Always Harm Agroecosystem Services? A Global Synthesis - Yunfei Ren; Xiaodong Liu; Haibo Hu; Dayu Liu; Nannan Li; Xunan Li; Fei Mo (Global Change Biology, 2025)
Microplastics (MPs) are an emerging global change factor with the potential to affect key agroecosystem services. Yet, MPs enter soils with highly variable properties (e.g., type, shape, size, concentration, and aging duration), reflecting their heterogeneous chemical compositions and diverse sources. The impacts of MPs with such varying properties on agroecosystem services remain poorly understood, limiting effective risk assessment and mitigation efforts. We synthesized 6315 global observations to assess the broad impacts of microplastic properties on key agroecosystem services, including crop productivity and physiology, soil carbon sequestration, nutrient retention, water regulation, and soil physical and microbial properties. MPs generally caused significant declines in aboveground productivity, crop physiology, water‐holding capacity, and nutrient retention. However, the direction and magnitude of these effects varied considerably depending on the specific properties of MPs. The hazards posed by MPs to aboveground productivity, antioxidant systems, and root activity were size‐ and dose‐dependent, with larger particles at higher concentrations inducing greater damage. Prolonged microplastic exposure impaired crop photosynthesis and soil nutrient retention, but most other ecosystem services (e.g., belowground productivity, antioxidant systems, and root activity) showed gradual recovery over time. Fiber‐shaped MPs positively influenced crop aboveground and belowground productivity and soil carbon sequestration, potentially due to their linear configuration enhancing soil aggregation and connectivity. Polymer type emerged as the most prominent driver of the complex and unpredictable responses of agroecosystem services to MPs, with biodegradable polymers unexpectedly exerting larger negative effects on crop productivity, root activity, photosynthesis, and soil nutrient retention than other polymers. This synthesis underscores the critical role of microplastic properties in determining their ecological impacts, providing essential insights for property‐specific risk assessment and mitigation strategies to address microplastic pollution in agroecosystems.

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Macrophage membrane-based biomimetic nanocarrier system for enhanced immune activation and combination therapy in liver cancer - Wei Ni; Mingzhu Zhang; Yueni Mo; Wei Du; Hui Liu; Zhaosong Wang; Yanfen Cui; He Zhang; Zhiyong Wang; Liming Liu; Hui Guo; Ruifang Niu; et al. (Drug Delivery and Translational Research, 2025)

Lactiplantibacillus plantarum T34 alleviates constipation by enhancing intestinal barrier and modulating gut homeostasis - Fei Shen; Huiting Zhu; Zhongyan Bao; Di Han; Juan Du; Minjie Zhao; Fengqin Feng; Guanghua He; Qiufen Mo (Food Bioscience, 2025)

Towards new bioactive fluorine-containing 1,3,4-oxadiazole-amide derivatives: synthesis, antibacterial activity, molecular docking and molecular dynamics simulation study - Fei Xiong; Yanjun Zhang; Jinlong Jiao; Yiren Zhu; Tianlu Mo; Yeji Li (Molecular Diversity, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Biochar strategy for long-term N2O emission reduction: Insights into soil physical structure and microbial interaction - Yeye Zhang; Chun Yan; Tao Wang; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Soil Biology and Biochemistry, 2025)

Analysis of soil bacterial diversity and effective control of mango anthracnose - Xiaohu Wang; Shuang He; Rui Wang; Xin Liu; Tingting Mo; Qi fei Liu; Liujian Ye; Qixia Zhu; Shengbo Wei; Jianzong Meng; Hongmei Gao; Liqin Zhou (Physiological and Molecular Plant Pathology, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Probing the potential microbiota-mediated effects of sodium dehydroacetate on hyperphagia and inflammation in mice - Qiufen Mo; Fei Shen; Shengyue Ruan; Junhui Zhang; Minjie Zhao; Fengqin Feng; Tao Liu (Food Bioscience, 2025)

Turbulence scale and strength analysis in the roughness and inertial sublayers over urban areas: A wind tunnel study - Fei Li; Ruiqi Wang; Guoliang Chen; Ziwei Mo; Naoki Ikegaya; Chun-Ho Liu (Building and Environment, 2025)

Impaired inducibility of immune regulatory capacity of peripheral B cells of patients with recurrent pregnancy loss - Fei Ma; Xiaoyang Feng; Shiyu Feng; Jin Liu; Jia Li; Lihua Mo; Lingzhi Xu; Yulei Liu; Jiaman Wu; Pingchang Yang; Yan Ning (Immunologic Research, 2024)

Towards equitable infrastructure asset management: Scour maintenance strategy for aging bridge systems in flood-prone zones using deep reinforcement learning - Amir Taherkhani; Weiwei Mo; Erin Bell; Fei Han (Sustainable Cities and Society, 2024)

Microbial life-history strategies and particulate organic carbon mediate formation of microbial necromass carbon and stabilization in response to biochar addition - Yeye Zhang; Tao Wang; Chun Yan; Yuze Li; Fei Mo; Juan Han (Science of The Total Environment, 2024)

Bone Marrow Mesenchymal Stem Cell-Derived Exosomes Alleviate Nuclear Pulposus Cells Degeneration Through the miR-145a-5p/USP31/HIF-1α Signaling Pathway - Kang-Kang Su; De-Chen Yu; Xiong-Fei Cao; Pan Li; Le Chang; Xiao-Lei Yu; Zhi-Quan Li; Mo Li (Stem Cell Reviews and Reports, 2024)

Microplastics positively mediate soil multifunctionality in dryland - Peng-Yang Wang; Ze-Ying Zhao; Kadambot H.M. Siddique; Xiao-Bin Xiong; Hong-Yan Tao; Yue Ma; Fei Mo; Yinglong Chen; Yajie Song; William R. Burch; Baoluo Ma; Song Wang; et al. (Resources, Conservation and Recycling, 2024)

Seven-year long-term inoculation with Funneliformis mosseae increases maize yield and soil carbon storage evidenced by in situ 13C-labeling in a dryland - Meng-Ying Li; Wei Wang; Fei Mo; Ai-Tian Ren; Zhi-Ye Wang; Ying Zhu; You-Cai Xiong (Science of The Total Environment, 2024)

A novel algorithm to extrapolate ultraviolet absorption of chromophoric dissolved organic matter from remote sensing ocean color - Zhongli Liu; Shansheng Mo; Fei Liu; Gregory Korshin; Mingquan Yan (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

In-situ constructing ultrafine NiCo alloy confined in LDH nanoflower for efficient selective hydrogenation of furfural - Huiling Zhang; Jingnan Yang; Teng Zhao; Fujun Lan; Yixin Luo; Fei Han; Xianliang Qiao; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2024)

Assessing the impact of climate and crop diversity on regional greenhouse gas emissions and water demand of cropland - Yihe Tang; Shikun Sun; Yuhan Lei; Fei Mo; Jinfeng Zhao; Chong Li; Jiajun Tong; Yali Yin; Yubao Wang (Agricultural and Forest Meteorology, 2024)

Changes in microbial community and network structure precede shrub degradation in a desert ecosystem - Guohua Wang; Seth M. Munson; Elly Morriën; Fei Mo; Mengting Maggie Yuan; Bin Wang; Ning Chen; Jian-Sheng Ye; Kailiang Yu (CATENA, 2024)

Developing cellulose-based hydrophobic/hydrophilic composites for efficient adsorption of oils and heavy metals from water - Fengqin Yin; Dianli Zhou; Yeling Mo; Junjie Zhu; Yunyan Zhang; Hui Cao; Min Yuan; Tai Ye; Fei Xu (Science of The Total Environment, 2024)

Orbital forcing of aridity/humidity fluctuations in the Hexi Corridor and Alxa Plateau, NW China, during the last 1.8 million years - Dianbao Chen; Jiaming Yang; Junsheng Nie; Fei Wang; Qinhong Mo; Baotian Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Nutrient limitation of soil organic carbon stocks under straw return - Fei Mo; Dayang Yang; Xiukang Wang; Thomas W. Crowther; Nangia Vinay; Zhongkui Luo; Kailiang Yu; Shikun Sun; Feng Zhang; Youcai Xiong; Yuncheng Liao (Soil Biology and Biochemistry, 2024)

RETRACTED: Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Soybean-processing wastewater as an electron donor for denitrification - Yue Ma; Chong Tan; Songyun Chen; Haiyun Zhang; Fei Liu; Xu Peng; Mo Li; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Turbulent transport mechanism in the roughness sublayers over idealized urban areas and its implication to street-level ventilation - Ruiqi Wang; Chun-Ho Liu; Fei Li; Ziwei Mo (Sustainable Cities and Society, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Responses of wheat nitrogen uptake and utilization, rhizosphere bacterial composition and nitrogen-cycling functional genes to nitrogen application rate, planting density and their interactions - Zimeng Liang; Jiayu Li; Xidan Cao; Yangyang Tang; Fei Mo; Vinay Nangia; Yang Liu (Applied Soil Ecology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Strontium alleviated the growth inhibition and toxicity caused by cadmium in rice seedlings - Jun Liu; Xinting Fan; Yuanyuan Jiang; Juan Ni; Aili Mo; Meihan Cai; Tong Li; Yaqi Wang; Peishuang He; Shiyu Hu; Tangjian Peng; Cuiying Peng; et al. (Science of The Total Environment, 2023)

Cadmium affects the growth, antioxidant capacity, chlorophyll content, and homeostasis of essential elements in soybean plants - Jun Liu; Juan Ni; Aili Mo; Xinting Fan; Yuanyuan Jiang; Hongyan Xie; Jingsong Hu; Yunhua Zhu; Cuiying Peng; Fei Yang (South African Journal of Botany, 2023)

Exploring the mechanism by which quercetin re-sensitizes breast cancer to paclitaxel: network pharmacology, molecular docking, and experimental verification - Ye Yang; Jiaoyan Yan; Jian Huang; Xiangyi Wu; Yan Yuan; Yan Yuan; Shu Zhang; Fei Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Identification and functional characterization of REGULATORY PARTICLE NON-ATPASE 1a-like (AhRPN1a-like) in peanuts during aluminum-induced programmed cell death - Guoting Liao; Shuzhen Luo; Xinyue Li; Ailing Li; Yunchuan Mo; Aiqin Wang; Dong Xiao; Long-Fei He; Jie Zhan (Journal of Plant Physiology, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

A pilot study on glutamate receptor and carrier gene variants and risk of childhood autism spectrum - Jun Liu; Jing Yan; Fei Qu; Weiming Mo; Hong Yu; Pingfang Hu; Zengyu Zhang (Metabolic Brain Disease, 2023)

Research development on electrolytes for magnesium-ion batteries - Yuehua Man; Pauline Jaumaux; Yifan Xu; Yating Fei; Xiangyin Mo; Guoxiu Wang; Xiaosi Zhou (Science Bulletin, 2023)

IL8 of Takifugu rubripes is a chemokine that interacts with peripheral blood leukocytes and promotes antibacterial defense - Hong-qiang Zhang; Xiao-yan Jin; Xue-peng Li; Mo-fei Li (Fish & Shellfish Immunology, 2023)

Global depth distribution of belowground net primary productivity and its drivers - Liujun Xiao; Guocheng Wang; Jinfeng Chang; Yaoyao Chen; Xiaowei Guo; Xiali Mao; Mingming Wang; Shuai Zhang; Zhou Shi; Yiqi Luo; Lei Cheng; Kailiang Yu; et al. (Global Ecology and Biogeography, 2023)
Aim This study aimed to infer the allocation of belowground net primary productivity (BNPP) to sequential soil depths down to 2 m across the globe at a 1 km resolution and assess underlying environmental drivers. Location Global. Time Period Contemporary (1932–2017). Major Taxa Studied Terrestrial plants. Methods Global datasets including field net primary production (NPP, i.e., the difference between plant assimilated and respired carbon) from 725 soil profiles, root biomass and its depth distribution from 559 soil profiles were compiled and used to infer the depth distribution of BNPP across the globe and digitally map depth‐resolved BNPP globally at 1 km resolution. Drivers of the depth distribution of BNPP were evaluated using machine learning‐based models. Results Global average BNPP allocated to the 0–20 cm soil layer is estimated to be 1.1 Mg C ha −1 yr −1 , accounting for ~60% of total BNPP. Across the globe, the depth distribution of BNPP varies largely, and more BNPP is allocated to deeper layers in hotter and drier regions. Edaphic, climatic and topographic properties (in order of importance) explain >80% of such variability; and the direction and magnitude of the influence of individual properties are soil depth‐ and biome‐dependent. Main Conclusions The findings suggest that mean annual temperature and precipitation are the two most important factors regulating BNPP across the globe. Soil properties such as soil actual evaporation and total nitrogen also play a vital role in regulating the depth distribution of BNPP. The maps of BNPP provide global benchmarks of depth‐resolved BNPP for the prediction of whole‐profile soil carbon dynamics across biomes.

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Evading the permeance-selectivity trade-off dilemma in electrospray-assisted interfacial polymerization polyamide thin-film composite membrane through electrospinning nanofibers interlayer - Jia-Hao Liu; Fei Xie; Han-Zhuo Ding; Jia-Wei Mo; Xiao-Gang Jin; Xiao-Hua Ma; Zhen-Liang Xu (Desalination, 2023)

Alkanolamines-activated steel slag for stabilization/solidification of heavy metal contaminated soil - Bin Zeng; Zhi Zhang; Shuo Yang; Liwu Mo; Fei Jin (Journal of Environmental Chemical Engineering, 2023)

An ultra-sensitive and selective electrochemical sensor based on GOCS composite and ion imprinted polymer for the rapid detection of Cd2+ in food samples - Fengqin Yin; Yeling Mo; Xueting Liu; Hongzhi Yang; Dianli Zhou; Hui Cao; Tai Ye; Fei Xu (Food Chemistry, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Edwardsiella piscicida Ail1: An outer membrane protein required for host infection - Mo-fei Li; Yu-ting Du; Cheng-dong Jin; Xue-peng Li; Yuan-yuan Sun (Aquaculture, 2023)

Genome mining-guided activation of two silenced tandem genes in Raoultella ornithinolytica XF201 for complete biodegradation of phthalate acid esters - Nai-Xian Feng; Fei Zhang; Yunchang Xie; Hui Bin; Lei Xiang; Yan-Wen Li; Fantao Zhang; Yunhong Huang; Hai-Ming Zhao; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Science of The Total Environment, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Soil tillage rather than crop rotation determines assembly of the wheat rhizobacterial communities - Tong Li; Huanxin Xie; Zhangheng Ren; Yuting Hou; Deqiang Zhao; Weiyan Wang; Ziting Wang; Yang Liu; Xiaoxia Wen; Juan Han; Fei Mo; Yuncheng Liao (Soil and Tillage Research, 2023)

Research on health risk assessment of heavy metals in soil based on multi-factor source apportionment: A case study in Guangdong Province, China - Jiahui Liang; Zhaoyue Liu; Yiqi Tian; Huading Shi; Yang Fei; Jingxian Qi; Li Mo (Science of The Total Environment, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

A novel C1qDC (PoC1qDC) with a collagen domain in Paralichthys olivaceus mediates complement activation and against bacterial infection - Mo-fei Li; Hong-qiang Zhang; Jin-sheng Sun (Fish & Shellfish Immunology, 2023)

Porous Cobalt-nickel phosphides prepared from Al-doped NiCo-LDH precursors for supercapacitor and electrocatalysis applications - Ruonan Liu; Lulu Chen; Fei Mo; Haiyan Song; Guang Yang; Chunxia Chen; Xiaoliang Wu; Yichao Huang; Zhuangjun Fan (Chemical Engineering Journal, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Global pattern of soil priming effect intensity and its environmental drivers - Fei Mo; Chengjie Ren; Kailiang Yu; Zhenghu Zhou; Richard P. Phillips; Zhongkui Luo; Yeye Zhang; Yuteng Dang; Juan Han; Jian‐Sheng Ye; Nangia Vinay; Yuncheng Liao; et al. (Ecology, 2022)
The microbial priming effect—the decomposition of soil organic carbon (SOC) induced by plant inputs—has long been considered an important driver of SOC dynamics, yet we have limited understanding about the direction, intensity, and drivers of priming across ecosystem types and biomes. This gap hinders our ability to predict how shifts in litter inputs under global change can affect climate feedbacks. Here, we synthesized 18,919 observations of CO 2 effluxes in 802 soils across the globe to test the relative effects (i.e., log response ratio [RR]) of litter additions on native SOC decomposition and identified the dominant environmental drivers in natural ecosystems and agricultural lands. Globally, litter additions enhanced native SOC decomposition (RR = 0.35, 95% CI: 0.32–0.38), with greater priming effects occurring with decreasing latitude and more in agricultural soils (RR = 0.43) than in uncultivated soils (RR = 0.28). In natural ecosystems, soil pH and microbial community composition (e.g., bacteria: fungi ratio) were the best predictors of priming, with greater effects occurring in acidic, bacteria‐dominated sandy soils. In contrast, the substrate properties of plant litter and soils were the most important drivers of priming in agricultural systems since soils with high C:N ratios and those receiving large inputs of low‐quality litter had the highest priming effects. Collectively, our results suggest that, though different factors may control priming effects, the ubiquitous nature of priming means that alterations of litter quality and quantity owing to global changes will likely have consequences for global C cycling and climate forcing.

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Effects of CYP24A1 polymorphisms on premature ejaculation: a case–control study - Fei Wang; Defan Luo; Jianxiang Chen; Cuiqing Pan; Zhongyao Wang; Housheng Fu; Jiangbing Xu; Meng Yang; Shaowei Mo; Liying Zhuang; Weifu Wang (Journal of Genetics, 2022)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

The role of T-LAK cell-originated protein kinase in targeted cancer therapy - Lu Zhang; Fei Wang; Huijun Yi; Svetlana P. Ermakova; Olesya S. Malyarenko; Jianmei Mo; Yingze Huang; Qiuhong Duan; Juanjuan Xiao; Feng Zhu (Molecular and Cellular Biochemistry, 2022)

Cytochalasins from endophytic Diaporthe sp. GDG-118 - Xishan Huang; Dexiong Zhou; Yan Liang; Xiaobo Liu; Fei Cao; Yuyue Qin; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Study on synthesis and anticancer activity of 17beta-estradiol-phenol/aniline nitrogen mustard derivatives - Yu-dong Yin; Jing-jing Liu; Wen-fei Liao; Xian-kun Guo; Li-shan Zhang; Wei-bin Mo; Ke-guang Cheng (Medicinal Chemistry Research, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Microbial carbon-use efficiency and straw-induced priming effect within soil aggregates are regulated by tillage history and balanced nutrient supply - Fei Mo; Ye-Ye Zhang; Yang Liu; Yun-Cheng Liao (Biology and Fertility of Soils, 2021)

The effect of follower load on the range of motion, facet joint force, and intradiscal pressure of the cervical spine: a finite element study - Xin-Yi Cai; Chen-Xi YuChi; Cheng-Fei Du; Zhong-Jun Mo (Medical & Biological Engineering & Computing, 2020)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Pathogenicity of an FAdV-4 isolate to chickens and its genomic analysis - Kai-kun Mo; Chen-fei Lyu; Shang-shang Cao; Xia Li; Gang Xing; Yan Yan; Xiao-juan Zheng; Min Liao; Ji-yong Zhou (Journal of Zhejiang University-SCIENCE B, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Detection of lncRNA-mRNA interaction modules by integrating eQTL with weighted gene co-expression network analysis - Xing-Bo Mo; Long-Fei Wu; Xin Lu; Xiao-Wei Zhu; Wei Xia; Lan Wang; Pei He; Peng-Fei Bing; Yong-Hong Zhang; Fei-Yan Deng; Shu-Feng Lei (Functional & Integrative Genomics, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

Detecting and attributing vegetation changes in Taihang Mountain, China - Shi Hu; Fei-yu Wang; Che-sheng Zhan; Ru-xin Zhao; Xiong-guo Mo; Liang-mei-zi Liu (Journal of Mountain Science, 2019)

Surface mulching and a sandy soil interlayer suppress upward enrichment of salt ions in salt-contaminated field - Jianyong Wang; Huiming Liu; Shaoming Wang; Yingxia Liu; Zhengguo Cheng; Guangqiang Fu; Fei Mo; Youcai Xiong (Journal of Soils and Sediments, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Enhanced production of heterologous proteins by Bacillus licheniformis with defective d-alanylation of lipoteichoic acid - Yaozhong Chen; Dongbo Cai; Penghui He; Fei Mo; Qing Zhang; Xin Ma; Shouwen Chen (World Journal of Microbiology and Biotechnology, 2018)

The distribution and functional relevance analysis of runs of homozygosity (ROHs) in Chinese Han female population - Yi-Hua Lu; Bing-Hua Wang; Wei Xia; Xing-Bo Mo; Long-Fei Wu; Xiao-Wei Zhu; Pei He; Fang-Fei Xie; Xin Lu; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Toxicological effects of microcystin-LR on earthworm (Eisenia fetida) in soil - Hong-Fei Wen; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Lei Chen; Quan-Ying Cai; Hui Li; Ce-Hui Mo; Dong-Mei Zhou; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Single Nucleotide Polymorphisms in SLC19A1 and SLC25A9 Are Associated with Childhood Autism Spectrum Disorder in the Chinese Han Population - Jun Liu; Weiming Mo; Zengyu Zhang; Hong Yu; Aiping Yang; Fei Qu; Pingfang Hu; Zhuo Liu; Shihu Wang (Journal of Molecular Neuroscience, 2017)

Modeling of Coal Fine Migration During CBM Production in High-Rank Coal - Su-Yang Zhu; Xiao-Long Peng; Zhi-Min Du; Chao-Wen Wang; Peng Deng; Fei Mo; Yu Lei; Mingwei Wang (Transport in Porous Media, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Comparative proteomic analysis of Phalaenopsis leaves in the vegetative and flowering phase - Xiu-Yun Yuan; Shen-Ping Xu; Fang Liang; Su-Hua Jiang; Mo-Fei Wang; Jie Ma; Xian-Yun Zhang; Bo Cui (Acta Physiologiae Plantarum, 2016)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Elevated DNA damage response in pancreatic cancer - Michael Osterman; Deion Kathawa; Diangang Liu; Huan Guo; Chao Zhang; Mo Li; Xiaochun Yu; Fei Li (Histochemistry and Cell Biology, 2014)

The protective roles of S-adenosylmethionine decarboxylase (SAMDC) gene in melon resistance to powdery mildew infection - Changming Liu; Xiaoling Li; Ruiping Yang; Yanling Mo; Yongqi Wang; Feng Xian; Xian Zhang; Fei Wang (Horticulture, Environment, and Biotechnology, 2014)

Spatiotemporal variations affect uptake of inorganic and organic nitrogen by dominant plant species in an alpine wetland - Jun-Qin Gao; Yi Mo; Xing-Liang Xu; Xue-Wen Zhang; Fei-Hai Yu (Plant and Soil, 2014)

Analysis of sequence variability in the pig CART gene and association of polymorphism with fatness traits in a F2 population - Xiaoping Zhu; Delin Mo; Chong Wang; Xiaohong Liu; Jiaqi Li; Fei Ling; Yaosheng Chen (Molecular Biology Reports, 2014)

Distribution and conservation status of Rhinopithecus strykeri in China - Ma Chi; Huang Zhi-Pang; Zhao Xiao-Fei; Zhang Li-Xiang; Sun Wen-Mo; Matthew B. Scott; Wang Xing-Wen; Cui Liang-Wei; Xiao Wen (Primates, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Molecular cloning, expression patterns and subcellular localization of porcine TMCO1 gene - Zhisheng Zhang; Delin Mo; Peiqing Cong; Zuyong He; Fei Ling; Anning Li; Yuna Niu; Xiao Zhao; Chunyan Zhou; Yaosheng Chen (Molecular Biology Reports, 2010)

Detection of Two Fungal Biocontrol Agents against Root-knot Nematodes by RAPD Markers - Ming Liang Zhu; Ming He Mo; Zhen Yuan Xia; Yun Hua Li; Shu Jun Yang; Tian Fei Li; Ke Qin Zhang (Mycopathologia, 2006)

Protecting the national parks and the world heritage sites in China: challenge and strategy - Zhang Baiping; Wu Hongzhi; Xiao Fei; Mo Shenguo (Journal of Geographical Sciences, 2004)

Digital spectra and analysis of altitudinal belts in Tianshan Mountains, China - Baiping Zhang; Shenguo Mo; Hongzhi Wu; Fei Xiao (Journal of Mountain Science, 2004)